(untitled) (Revista Espinhaço, 2017)
The article summarizes the main strategies and actions to develop the Jequitinhonha Valley, one of the poorest regions of Minas Gerais state in Brazil. It employs, as the main source, the Plan for the development of the Jequitinhonha Valley, elaborated by Fundação João Pinheiro. The region was marked by a long process of isolation, unable to insert in the dynamic sectors of Minas Gerais economy. The most important policy to trigger advances was the policies of income transfer adopted recently by the federal Government, which strongly resulted poverty and opened the possibilities for more consistent programs. The article departs from conceptual considerations about the meaning of development and the present specificities of the planning process. It emphasizes the importance of participation practices and of a multidimensional process of development, promoted simultaneously in several directions. The first one includes revitalization of rivers and water resources and the strengthening of infrastructure in transports, energy, telecommunications and sanitation. The second implies the advance of the agriculture and the economy, which demands policies of commercialization, technical assistance to producers, environment licensing and stimulus to the processing of primary goods by the small farmers. It also includes stimulus to certain industrial niches, to mining and to tourism, always in harmony with the environment. Finally, the article indicates the necessary directions to promote advances in the social area, including health, education, culture, social assistance and public security. They should be accompanied by progress in municipal administrations’ capacities and by a governance structure inspired in recent practices of territorial development